CP-077 Analysis of costs and prescription guidelines of etanercept and adalimumab in patients of rheumatology, dermatology and gastroenterology services on the pharmacy outpatient unit. (24th March 2015) - Martínez, S; Minguez, A; Garcia, JJ; Andres, M; Goitia, V; Martinez, C
Abstract : Background: Nowadays the physicians are changing TNF-blockers prescribing guidelines which influence the pharmaceutical expense. Purpose: To analyse adalimumab and etanercept prescriptions practice on the outpatient unit. Material and methods: Retrospective observational study in which patients of Rheumatology, Gastroenterology and Dermatology services were included. After analysing the total cost of etanercept and monoclonal antibodies used in these services during 2011 and 2013, a large variation was observed in expense, seeing a decrease of 18% in Rheumatology, an increase of 85% in Gastroenterology and an increase of 10% in Dermatology service. Therefore, in a first phase, we decided to analyse prescribing patterns of adalimumab and etanercept. The information was obtained from outpatient internal program, Global Clinic ® and SAP ® . Results: Regarding the expense on the outpatient unit, Reumathology service was the only one that reduced it between these years with a decrease of 15.1%. In Dermatology, an increase of 10% was observed; partly due to ustekinumab's dispensation (6 patients were treated in 2011 and 7 in 2013; moreover, in 2013 the administration regimen was more frequently than in 2011). In Gastroenterology service an increase of 63% was observed. The reason of this was the change in number of patients and in prescription guides, as noted in table 1. Conclusion: After analysing Hospital's prescribing guidelines of these two drugs, we could observe we have treated more patients in rheumatic diseases without increasing spending because of the less frequently administration of these drugs. In Dermatology service, we have more expense not due to adalimumab or etanercept drugs, probably ustekinumab instead. With the studied drugs we only treat two more patients administering them less frequently. Finally, in Gastroenterology service the expense has increased probably because more patients have been treated and not due to administration schedules. References and/or Acknowledgements: No No conflict of interest.